Earthquake Engineering & Structural Dynamics - Earthquake Engineering & Structural Dynamics (Wiley, 2026)
Earthquake Engineering & Structural Dynamics is a civil engineering journal publishing research in structural and geotechnical earthquake engineering. The journal is dedicated to building the knowledge needed to make structures more resistant to earthquakes, making the world a safer place.
FI 1.07
Q1
Keywords: Physical Sciences & Engineering; Structural & Building Engineering; Ingeniería estructural y edificación; Ingeniería Sísmica; Acuerdos transformativos; Transformative agreements; Ingeniería civil; Riesgo sísmico; Ingeniería de riesgos